1980
DOI: 10.1016/s0022-5347(17)55851-6
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Bladder Neck Dysfunction

Abstract: Bladder neck dysfunction has been evaluated in 16 male patients. The efficacy of the traditional investigative methods for this entity is questionable and the value of video-urodynamics for definitive diagnosis is presented. The ability of the condition to masquerade as prostatis is apparent and treatment by unilateral bladder neck incision is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Autonomic dysreflexia (AD) results from high level SCI above the sympathetic nucleus, whereas detrusor external sphincter dyssynergia (DESD) occurs in suprasacral cord injury [1, 2, 3, 4]. Injury to the sacral cords and cauda equina always results in an areflexic bladder and urethra at first, but later the bladder may develop gradually into a contracted, high-pressure and low-compliance state [5].…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic dysreflexia (AD) results from high level SCI above the sympathetic nucleus, whereas detrusor external sphincter dyssynergia (DESD) occurs in suprasacral cord injury [1, 2, 3, 4]. Injury to the sacral cords and cauda equina always results in an areflexic bladder and urethra at first, but later the bladder may develop gradually into a contracted, high-pressure and low-compliance state [5].…”
Section: Introductionmentioning
confidence: 99%
“…Research concerning the origin of these disorders has been directed towards the illumination of extra-prostatic etiologies. Uroflowmetry abnormalities are reported in 30% of the cases [2], Urodynamic testing in these patients has frequently shown functional disorders of the lower urinary tract: disorders of the bladder outlet [3]; detrusor hyperreflexia, and detrusor areflexia with nonre laxing pelvic floor striated musculature [4]. Pelvic floor tension myalgia due to habitual contraction and spasm has also been suggested as a possible cause [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Ronzoni and De Vecchis [8] and Abdel-Basir Sayed [15] also observed that the incidence of retrograde ejaculation in the patients who underwent bladder neck and prostate resection with preservation of the supramontanal tissue was significantly lower than that of the patients who had complete resection of the bladder neck and prostate. Kaplan et al [14] and Webster et al [16] reported that all the patients kept antegrade ejaculation after unilateral incision of the bladder neck. Since more prostatic tissue was preserved in the unilateral incision than that in the bilateral incision of the bladder neck, a higher incidence of antegrade ejaculation could be expected.…”
Section: Discussionmentioning
confidence: 99%